Removal of Mainbeam Jamming Signals With Dual-Compensation-Phase Coding Radar - Zhang, Xiang; Lan, Lan; Zhu, Shengqi; Liao, Guisheng; Li, Ximin (IEEE transactions on aerospace and electronic systems, 2025)
This article investigates the removal of mainbeam jamming signals using a dual-compensation-phase coding (DC-PC) radar. At the transmitter, the waveforms are simultaneously encoded in both transmit channels and slow-time, utilizing a coding coefficient and intrapulse index. In the receiver, based on the phase differences caused by time delay between the false and true targets, a dual compensation method is proposed to identify false targets from the true one in the transmit spatial frequency dimension, which enables the removal of mainbeam deceptive jamming signals through transmit–receive 2-D beamforming. Furthermore, in order to mitigate the performance degeneration due to the existence of direction of arrival (DOA) mismatch, a constrained optimization problem is established with the aim of maximizing the signal-to-interference-plus-noise ratio (SINR) with respect to both the coding coefficient and intrapulse index. In this regard, the alternating optimization (AO) procedure is utilized to tackle the problem, resorting to the majorization–minimization (MM) and gradient descent (GD) algorithms. The performance of removing mainbeam jamming signals in DC-PC radar is compared with other radar frameworks in terms of the Capon spectra, output power, and output SINR. Simulation results verify the superiorities of the devised methods in DC-PC radar.